Roots and nitrogen in cropping systems of the Semi- Arid tropics (Japan International Research Center for Agricultural Sciences, 1996)
This book is the proceedings of a workshop on roots and N dynamics in cropping systems of the semi-arid tropics, held in Patancheru, Hyderabad, India, in 1994, are presented. In 47 papers the following subjects are dealt with: (1) the significance of intercropping in various cropping systems; (2) the functions and morphology of root systems, and their changes in relation to genotypes of crops and environmental stresses such as excess and deficiency of moisture and nutrients; (3) the N input from biological-N fixation in relation to its balance with C input and N uptake; (4) the status and dynamics of N in soils and the effects of long-term cropping on the N budget, and effective ways of N management in intercropping; and (5) recent developments in modelling root growth, root interaction, crop growth, and the N budget in intercropping and in farming systems. The main cropping systems are pigeon pea-based systems as widely practised in India; other crops include chickpea, cotton, rice, sorghum, wheat, and white clover (Trifolium repens).